Public opinion - Seoane, Julio (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
This work try to show the history of public opinion in five stages ranging from its presentation in the XVIII with the Enlightenment to its new configuration with our social media, through the institution of public opinion in the liberal press of the nineteenth century, the issues of manipulation of the late nineteenth and early twentieth centuries and its status as a place of democracy in the second half of the twentieth.
Keywords: public; press; mass media; polls